Energy from agricultural products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Producing energy that does not pollute the environment, affect the climate or cost too much money seems a difficult task. However, today, new technologies are enabling energy to be generated from a number of agricultural residues.